Religion, Identity and Politics in the Age of Communication and Information Technologies with Emphasis on Iran - Garineh Keshishyan Sirki; Refika Mastanora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This article examines the concepts of religion, identity, and politics, as well as the concept of digital democracy and its impact on political participation in the information technology age. With the rapid growth of digital technologies and the expansion of online platforms, traditional forms of political participation have undergone fundamental changes that raise fundamental questions about the opportunities and threats to the progress of modern democracy. Opportunities such as increased access, facilitating communication between citizens and the government, greater transparency, and the participation of marginalized groups are examined. The role of technologies such as electronic voting, social media, blockchain, and artificial intelligence in improving democratic processes was considered. However, along with these opportunities, challenges such as the digital divide, the spread of misinformation, security risks, and privacy violations were also analyzed. Successful and unsuccessful case studies of the implementation of digital democracy in different countries, such as electronic voting and constitution writing through online participation, shed light on the practical dimensions of this phenomenon. Finally, the article emphasizes the need for smart policymaking, the development of media literacy, the protection of personal data, and the design of inclusive digital platforms to ensure that religion, culture, and identity are not compromised in the digital age. Continuous innovation, institutional adaptability, and collaboration between government, civil society, and technology companies are among the requirements for a successful transition to an inclusive, transparent, and sustainable digital democracy, although there is still a long way to go.